Interrelations of α- and β-amylase activity with starch, sugars, and culinary and nutritional quality attributes in sweetpotato storage roots - Amankwaah, V.A.; Williamson, S.; Olukolu, B.; Truong, V.-D.; Carey, E.E.; Ssali, R.T.; Yencho, George Craig (Wiley, 2024)
BACKGROUND Little information is available on α- and β-amylase activity and their associations with starch, sugars and other culinary qualities in sweetpotato. The objective of this study was to assess sweetpotato storage root α- and β-amylase activity in relation to starch, sugars, β-carotene content and storage root flesh color.